A possible Indian quarter at al-Baleed in the fourteenth-seventeenth centuries AD? - Newton, Lynne S.; Zarins, Juris (Proceedings of the Seminar for Arabian Studies, 2014)
Excavations at al-Baleed in 2011-2012 uncovered along the city's southern wall a unique structure hitherto unreported at similar and contemporaneous sites along the northern Indian Ocean littoral. Two small, rectangular plastered platforms, accessed by two parallel staircases, were constructed in the centre of a much larger formal building with multiple storage compartments, perhaps a warehouse. Along the north-eastern external face of the platform building over thirty locally carved limestone heads as well as equally numerous carved circular stone palettes and pierced weights were recorded. A large and formal ablution area just to the north of the warehouse may also be associated. The date of the complex is suggested by stratigraphy and other associated imported and local ceramics to between AD 1300 and 1600. A number of stone cist graves discovered west of the warehouse complex are distinct from the local Islamic al-Baleed cemeteries. Current strontium and other dietary isotope trace analyses from these inhumations may suggest the presence of foreign populations distinct from local groups. Thus, multiple lines of evidence support the possibility of identifying an Indian quarter located along the southern city wall. Historical records and archaeology associate al-Baleed with the horse trade and western Indian ports and states. The discovered carved heads suggest ritual practices at al-Baleed, which have hitherto been undocumented.